Conventional radiotherapy versus concurrent chemoradiotherapy versus accelerated radiotherapy in locoregionally advanced carcinoma of head and neck: Results of a prospective randomized trial. Issue 2 (22nd May 2015) - Ghosh–Laskar, Sarbani; Kalyani, Nikhil; Gupta, Tejpal; Budrukkar, Ashwini; Murthy, Vedang; Sengar, Manju; Chaukar, Devendra; Pai, Prathamesh; Chaturvedi, Pankaj; D'Cruz, Anil; Agarwal, Jaiprakash
Abstract: Background: The purpose of this study was to report the results of a phase III, 3‐arm, randomized trial comparing conventional radiotherapy (RT) to concurrent chemoradiotherapy (CRT) and accelerated RT in advanced head and neck squamous cell carcinoma (HNSCC). Methods: One hundred eighty‐six of 750 planned patients were randomized to receive one of the following treatment plans: RT (66–70 Gy/2 Gy fraction/5 fractions weekly; CRT of weekly cisplatin (30 mg/m 2 ) with the same RT dose; or accelerated RT alone of 66 to 70 Gy/2 Gy fraction/6 fractions weekly were available for analysis. The primary endpoint was locoregional control at 5 years. Results: The mean follow‐up was 54 months. Among the 3 arms, CRT showed superior locoregional control (49%; p  = .049). RT had lower grade ≥3 mucositis and late toxicity. Conclusion: CRT is associated with significantly better locoregional control as compared to RT and accelerated RT with higher but acceptable acute and late toxicities. © 2015 Wiley Periodicals, Inc. Head Neck 38: 202–207, 2016